Unveiling Motivational Factors Driving Nepali Students to Pursue Higher Education Abroad (OCEM Journal of Management, Technology & Social Sciences, 2024)
Students pursuing foreign degrees are an increasing trend and this trend is a debatable phenomenon in Nepal; Nepali undergraduates prefer foreign degrees over Nepali ones. This article examined the significant factors influencing for Nepali undergraduates to decide on seeking foreign degrees. This study applied a quantitative research approach along with the survey to view the social reality and collect data from one hundred and forty-six participants planning to go abroad for their higher studies. The survey questionnaire was used as a data collection tool and a simple random sampling method was used for this study. Principal Component Analysis was used for dimension reduction and then binary logistic regression was applied to find the association the factor driving Nepali students seeking foreign degree and their motivation. The findings indicate a positive association between broader career options and Nepalese Bachelor level students pursuing foreign degrees. But the results indicate no association between comprehensive education, progressive curriculum, prospects and growth, social influence, diverse and unique exposure, and degree relevancy and their motivation. The study’s findings imply that considering the motivational factors identified, adopting a holistic approach to higher education in Nepal could provide better support for Nepali students seeking for abroad study. This approach would foster their personal and professional development and contribute significantly to Nepal’s overall progress and advancement.